Safety and efficacy of fecal microbiota transplantation (FMT) as a modern adjuvant therapy in various diseases and disorders: a comprehensive literature review - Karimi, Mehdi; Shirsalimi, Niyousha; Hashempour, Zahra; Salehi Omran, Hossein; Sedighi, Eshagh; Beigi, Farzan; Mortezazadeh, Masoud (Frontiers in Immunology, 2024)
The human gastrointestinal (GI) tract microbiome is a complex and all-encompassing ecological system of trillions of microorganisms. It plays a vital role in digestion, disease prevention, and overall health. When this delicate balance is disrupted, it can lead to various health issues. Fecal microbiota transplantation (FMT) is an emerging therapeutic intervention used as an adjuvant therapy for many diseases, particularly those with dysbiosis as their underlying cause. Its goal is to restore this balance by transferring fecal material from healthy donors to the recipients. FMT has an impressive reported cure rate between 80% and 90% and has become a favored treatment for many diseases. While FMT may have generally mild to moderate transient adverse effects, rare severe complications underscore the importance of rigorous donor screening and standardized administration. FMT has enormous potential as a practical therapeutic approach; however, additional research is required to further determine its potential for clinical utilization, as well as its safety and efficiency in different patient populations. This comprehensive literature review offers increased confidence in the safety and effectiveness of FMT for several diseases affecting the intestines and other systems, including diabetes, obesity, inflammatory and autoimmune illness, and other conditions.